2008
DOI: 10.4137/bbi.s1075
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the RGG Box Motif in Shadoo: RNA-Binding and Signaling Roles?

Abstract: Using comparative genomics and in-silico analyses, we previously identified a new member of the prion-protein (PrP) family, the gene SPRN, encoding the protein Shadoo (Sho), and suggested its functions might overlap with those of PrP. Extended bioinformatics and conceptual biology studies to elucidate Sho’s functions now reveal Sho has a conserved RGG-box motif, a well-known RNA-binding motif characterized in proteins such as FragileX Mental Retardation Protein. We report a systematic comparative analysis of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 94 publications
(75 reference statements)
4
35
0
Order By: Relevance
“…2a) indicate that the reduced transcriptional repression of RepSAA mutants compared with their non-mutated counterparts is not even a consequence of defects in nuclear localization. The relevance of the RGG sequence in the transcriptional repression activity, particularly evident in the Rep-130 context, is congruent with the role exerted by proteins containing RGG motifs (Alex & Lee, 2005;Corley & Gready, 2008). Interestingly, a lower repression of the AL1 gene transcription in vitro was reported for an RS-R125 mutant of TGMV Rep (where R125 of TGMV Rep corresponds to R124 of TYLCSV Rep) (Orozco et al, 2000).…”
Section: Role Of An Rgg Sequence In Tylcsv Repsupporting
confidence: 50%
See 1 more Smart Citation
“…2a) indicate that the reduced transcriptional repression of RepSAA mutants compared with their non-mutated counterparts is not even a consequence of defects in nuclear localization. The relevance of the RGG sequence in the transcriptional repression activity, particularly evident in the Rep-130 context, is congruent with the role exerted by proteins containing RGG motifs (Alex & Lee, 2005;Corley & Gready, 2008). Interestingly, a lower repression of the AL1 gene transcription in vitro was reported for an RS-R125 mutant of TGMV Rep (where R125 of TGMV Rep corresponds to R124 of TYLCSV Rep) (Orozco et al, 2000).…”
Section: Role Of An Rgg Sequence In Tylcsv Repsupporting
confidence: 50%
“…At amino acidic position 124-126 a highly conserved RGG triplet was noted, which was present in most sequences retrieved except for some New World species. Proteins with RGGbox motifs are involved in transcriptional repression and in binding and processing of RNA; these motifs are also typical of proteins localized in the nucleus/nucleolus (Burd & Dreyfuss, 1994;Godin & Varani, 2007;Corley & Gready, 2008). Since transcriptional repression, a process expected to take place in the nucleus, is fundamental for the resistance conferred by Rep-210 and Rep-130, we focused on this RGG sequence and tested its role in the subcellular localization and in the inhibition of the C1-gene transcription and TYLCSV replication by using truncated Rep mutants with the RGG sequence substituted by SAA (Rep-210SAA and Rep-130SAA).…”
mentioning
confidence: 99%
“…48 In general, the RGG box domain is characterized as having two or three RGG repeats, with five to nine residues separating the repeats, and has been identified in 44 human proteins. 49, 50 FMRP has been shown to use its RGG box domain to bind mRNA targets that form G quadruplex structures (Table 1). 19, 24, 2729, 33, 34, 51, 52 However, with the exception of the 5′-UTRs from microtubule associated protein 1B (MAP1B) mRNA, 27, 40 the protein phosphatase 2A catalytic subunit mRNA, 39 and the hASH1 mRNA 5′-UTR, 48 characterization of the FMRP RGG box binding G quadruplex structures has focused on coding region and 3′-UTR locations.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the N-terminus of PrP C and Shadoo possesses a conserved physiological activity. Recently, published data have revealed that the Shadoo N-terminal domain (and especially the RGG-box region) can also bind nucleic acids, especially RNAs (Lau and Westaway Prion 2010 conference, Salzburg; [71]) suggesting that this domain is most certainly involved in HIV-1 inhibition. The role of Shadoo in the cell defense against viral injury should be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%